Drinking Outcomes Following Drink Refusal Skills Training: Differential Effects for African American and Non-Hispanic White Clients - Witkiewitz, Katie (2011)
Determining whether a particular treatment works for specific groups of people can help tailor dissemination of evidence-based alcohol treatments. It has been proposed that individuals from different racial groups might have better outcomes in treatments that are sensitive to sociocultural issues that impact alcohol use among these groups. The current study was a secondary analysis of data from the combined behavioral intervention (CBI) condition of the COMBINE study. Those randomly assigned to CBI (n = 776) had the opportunity to receive up to 9 skills training modules, which were chosen by the therapist. The goal of the current study was to determine whether receiving 1 of the CBI modules, drink refusal and social pressure skills training, predicted differential outcomes among African American clients. Results indicated that African American clients who received the drink refusal skills training module (n = 25) had significantly fewer heavy drinking days (d = 0.79) 1 year following treatment than African Americans clients who did not receive the module (n = 35). African American clients who received the module also had significantly fewer heavy drinking days (d = 0.86) than non-Hispanic White clients who received the module (n = 241). Good clinical outcomes at 1 year post treatment were observed among 80% of African Americans who received the module, compared with 54% of African Americans who did not receive the module and 52% of non-Hispanic White clients who did receive the module. Although small sample size limits interpretation, findings provide preliminary evidence supporting the inclusion of drink refusal skills training as part of alcohol interventions for African American clients.